2022
DOI: 10.1558/ijsll.20446
|View full text |Cite
|
Sign up to set email alerts
|

A segmentally informed solution to automatic accent classification and its advantages to forensic applications

Abstract: Traditionally, work in automatic accent recognition has followed a similar research trajectory to that of language identification, dialect identification and automatic speaker recognition. The same acoustic modelling approaches that have been implemented in speaker recognition (such as GMM-UBM and i-vector-based systems) have also been applied to automatic accent recognition. These approaches form models of speakers’ accents by taking acoustic features from right across the speech signal without knowledge of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The authors reported results of 94.8% precision and 49.2% recall for detecting incorrectly stressed words in the English L2 speech of Baltic and Slavic speakers. In [16], automatic accent classification was performed and its use in forensic applications was described.…”
Section: Related Workmentioning
confidence: 99%
“…The authors reported results of 94.8% precision and 49.2% recall for detecting incorrectly stressed words in the English L2 speech of Baltic and Slavic speakers. In [16], automatic accent classification was performed and its use in forensic applications was described.…”
Section: Related Workmentioning
confidence: 99%